El Recurso de Apelación y la Presunción de Inocencia en las Contravenciones Flagrantes ¿Detención o Caución - Erazo Tinoco, Diana Elizabeth (2016)
In the trial of flagrant contraventions of type, applying Resolution No. 01-2016 THE PLENARY SESSION OF THE NATIONAL COURT, THE CONSTITUTIONAL PRINCIPLE, the presumption of innocence of the alleged offender is violated, since the appeal for appeal, the alleged offender is deprived of his liberty in violation of the constitutional principle of the presumption of innocence. Is unconstitutional because if a person is caught in flagrant contravention, the adjudication hearing will be within 24 hours, which is the time it is stopped the offender, but it turns out that when the judge passes sentence (not executory) the offender has three days to challenge the judge's decision through an appeal, but the commencement of this action under resolution No. 01-2016 the PLENARY SESSION of the NATIONAL courts, does not mean freedom of contraventor the problem is this time of the filing of the appeal, since it is violating the presumption of innocence of the offender to keep a custodial sentence; and on the route that keep stopped if the offender works, you may even lose his job by not calling into the institution that works, so I think that in that journey that takes the handling of the appeal, the offender can sustituírsele preventive detention by any of the alternatives or alternative modalities (bond), as stipulated in Article 543 of the Code of Criminal Integral (COIP): 6 The bond will be available to ensure the presence of the accused person and suspend the effects of preventive detention. The bond may be money, policy, bond, pledge, mortgage or letter of guarantee from a financial institution. The accused person may pay bail with money or property or those of a guarantor ". The presumption is the knowledge that is acquired or inference or deduction under the reasoning draws judge the body of evidence in relation to other proofs which are held within the process, and that lead him to conclude that the unknown fact is true. Given that the Preliminary Book of the Code General Process (COIP), in Chapter Two, addresses the Guiding Principles and Guarantees in Criminal Proceedings. And Art. 5, points 21 and including procedural principles, that of innocence. "Section 5. Principles presale’s.- The right to due process of law, without prejudice to others established in the Constitution of the Republic, international instruments ratified by the State or other legal rules shall be governed by the following principles: (...) 3: "Duda favor of the defendant: the or the judge to convict, must have the conviction criminal culpability of the accused person beyond reasonable doubt". (...) 4. Innocence any person maintains his innocence and legal status should be treated as such, while a sentence determined otherwise not ejecutoríe" It should be noted that in view of this principle, the defendant is not required to submit any evidence to prove his innocence, and instead orders the 7 competent judicial authorities, the evidence of guilt of the accused; remembering that to convict. So that the constitutional presumption of innocence requires that the defendant be treated as innocent in the substantiation process; this is to recognize the right to remain free during the process, that is to consider that the accused can not be subjected to a penalty, and therefore cannot be treated as guilty until the final judgment of conviction was not handednd